The last gathering = Bazm-i aakhir : a vivid portrait of life in the red Fort - Faizuddin, Munshi; Farouqui, Ather (New Delhi : Roli Books, 2021)
Short account of life of the kings and princes during the regime of Bahadur Shah, II, King of Delhi.
Includes bibliographical references.
Translated from Urdu.
Keywords: Zafar, Bahadur Shah